Menghadapi Badai Digital : Studi Eksploratif Tentang Peran Big Data dalam Komunikasi Krisis - Deva Fitri Zuya; Mareta Rindiani; Sri Rapida; Nurbaiti Nurbaiti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study explores the role of Big Data in crisis communication in the digital age, where information dissemination happens quickly through various platforms. This transformation poses challenges such as the risk of spreading fake news and reputation crises. Big Data plays an important role in detecting potential crises early, as well as in understanding the dynamics of public opinion and designing more responsive and effective communication strategies. Through real-time data collection and analysis from various sources, such as social media and news reports, organizations can build smart and adaptive monitoring systems. This research uses a descriptive qualitative approach to explore the role of Big Data in crisis communication in the digital era. The results show that the crisis detection process starts from data collection, cleaning, to sentiment analysis that helps organizations measure public response. However, the application of Big Data also faces considerable challenges, including the complexity of processing data with high accuracy, privacy issues, and the readiness of infrastructure and human resources in the organization. This research provides clearer insights into the strategies that can be used to optimize Big Data in crisis communications, so that organizations can strengthen communication effectiveness, maintain reputation, and build public trust amidst evolving information challenges.